M1 macrophage-membrane-cloaked paclitaxel/β-elemene nanoparticles targeting cervical cancer for enhanced therapy - Yi Wang; Jiakun Wang; Chengbo Huang; Yang Ding; Leyao Lv; Yuhao Zhu; Nuo Chen; Yingyi Zhao; Qing Yao; Shengjie Zhou; Mei Chen; Qibing Zhu; et al. (Elsevier, 2024)
Cervical cancer is a leading cause of cancer-related mortality in females worldwide, necessitating urgent solutions for effective treatment. Paclitaxel (PTX), a natural diterpene alkaloid compound, has the ability to inhibit mitosis and induce programmed apoptosis in tumor cells. However, its toxicity and drug resistance limit its efficacy in certain cervical cancer patients. β-elemene (β-ELE) can reverse multidrug resistance by inhibiting ATP-binding cassette transporters, thereby enhancing chemotherapy drug retention. Therefore, we propose a combination therapy using PTX/β-ELE to improve chemotherapy sensitivity. To enhance targeted drug delivery, we developed M1-macrophage-membrane-coated nanoparticles (M1@PLGA/PTX/β-ELE) for co-delivery of PTX&β-ELE. Through both in vitro and in vivo cervical cancer models, we demonstrated that M1@PLGA/PTX/β-ELE effectively suppressed tumor progression and polarization of tumor-associated macrophages. Furthermore, H&E staining confirmed the high therapeutic biosafety of M1@PLGA/PTX/β-ELE as there was no significant damage observed in major organs throughout the entire therapeutic process. Overall, this study presents a targeted biomimetic nanoplatform and combinatorial strategy that synergistically enhances chemosensitivity in malignant tumors.